Răspunsuri

2014-03-30T23:23:14+03:00
9x-6y+4x-6y=1     ⇒   13x-12y=1      pe cea de sus o inmultim cu +12 iar pe cea de jos 
6x-4y+6x-9y=-1          12x-13y=-1      cu -13 si ⇒                                                                                                                                                                                                    156x-144y=12      ⇒          25y=25 ⇒  y=1  si 13x-12*1=1 ⇒   13x=13 ⇒x=1                -156x+169y=13                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                            
1 3 1